Effect of sequential medium with fibroblast growth factor-10 and follicle stimulating hormone on in vitro development of goat preantral follicles - Almeida, Anderson Pinto; Magalhães-Padilha, Deborah de Melo; Araújo, Valdevane Rocha; Costa, Sibele Lima da; Chaves, Roberta Nogueira; Lopes, Claudio Afonso Pinho; Donato, Mariana Aragão Matos; Peixoto, Christina Alves; Campello, Claudio Cabral; Buratini Junior, José [UNESP]; Figueiredo, José Ricardo de (Elsevier B.V., 2015)
A sequential medium with fibroblast growth factor-10 (FGF-10) and follicle stimulating hormone (FSH) was evaluated on the survival, ultrastructure, activation and growth rate of caprine preantral follicles submitted to long-term culture, aiming to establish an ideal in vitro culture system. Ovarian fragments were cultured for 16 days in alpha-MEM alone or supplemented with FGF-10 and/or FSH added sequentially on different days of culture. Ovarian fragments were cultured during the first (days 0-8) and second (days 8-16) halves of the culture period, generating 10 treatments: alpha-MEW+/alpha-MEM+ (cultured control), FSH/FSH, FSH/FGF-10, FSH/FSH + FGF-10, FGF-10/FGF-10, FGF-10/FSH, FGF-10/FSH + FGF-10, FSH + FGF-10/FSH + FGF-10, FSH + FGF-10/FSH and FSH + FGF-10/FGF-10. Follicle morphology, viability and ultrastructure were analyzed. The FSH/FGF-10 treatment showed a higher (P < 0.05) percentage of normal follicles compared to all other treatments. In addition, follicles from the FSH/FGF-10 treatment maintained ultrastructural integrity after the culture period. After 16 days of culture, the FSH/FGF-10 and FSH/FSH treatments showed a higher percentage of activation compared to the cultured control (alpha-MEW+/alpha-MEM+). Moreover, the FSH/FGF-10 treatment promoted greater follicular and oocyte diameters compared to the fresh control. In conclusion, this study showed that a sequential medium with FSH followed by FGF-10 (FSH/FGF-10 and FSH/FSH) maintains follicular viability and ultrastructure and promotes transition from the primordial to primary stage (activation) and growth in goat preantral follicles cultured in vitro.
Keywords: Caprine; Folliculogenesis; FSH; FGF-10; Preantral follicle